Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let us solve this step-by-step.
Given Function:
[tex]\[ f(x) = 3x^2 + 2 \][/tex]
Known Values:
[tex]\[ a = 2 \][/tex]
[tex]\[ h = 1 \][/tex]
### Part (a) - Find [tex]\( f(a) \)[/tex]
To find [tex]\( f(a) \)[/tex], we substitute [tex]\( a = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(a) = f(2) = 3(2)^2 + 2 \][/tex]
[tex]\[ f(2) = 3 \cdot 4 + 2 \][/tex]
[tex]\[ f(2) = 12 + 2 \][/tex]
[tex]\[ f(2) = 14 \][/tex]
So, [tex]\( f(a) = 14 \)[/tex].
### Part (b) - Find [tex]\( f(a+h) \)[/tex]
To find [tex]\( f(a+h) \)[/tex], we substitute [tex]\( a = 2 \)[/tex] and [tex]\( h = 1 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(a + h) = f(2 + 1) = f(3) \][/tex]
[tex]\[ f(3) = 3(3)^2 + 2 \][/tex]
[tex]\[ f(3) = 3 \cdot 9 + 2 \][/tex]
[tex]\[ f(3) = 27 + 2 \][/tex]
[tex]\[ f(3) = 29 \][/tex]
So, [tex]\( f(a+h) = 29 \)[/tex].
### Part (c) - Find [tex]\( \frac{f(a+h) - f(a)}{h} \)[/tex]
To find the difference quotient, we use the values for [tex]\( f(a) \)[/tex] and [tex]\( f(a+h) \)[/tex]:
[tex]\[ \frac{f(a+h) - f(a)}{h} = \frac{f(3) - f(2)}{1} \][/tex]
[tex]\[ \frac{f(3) - f(2)}{1} = \frac{29 - 14}{1} \][/tex]
[tex]\[ \frac{29 - 14}{1} = \frac{15}{1} \][/tex]
[tex]\[ \frac{15}{1} = 15 \][/tex]
So, [tex]\( \frac{f(a+h) - f(a)}{h} = 15 \)[/tex].
### Summary
The answers to the questions are:
a.) [tex]\( f(a) = 14 \)[/tex]
b.) [tex]\( f(a+h) = 29 \)[/tex]
c.) [tex]\( \frac{f(a+h) - f(a)}{h} = 15 \)[/tex]
Given Function:
[tex]\[ f(x) = 3x^2 + 2 \][/tex]
Known Values:
[tex]\[ a = 2 \][/tex]
[tex]\[ h = 1 \][/tex]
### Part (a) - Find [tex]\( f(a) \)[/tex]
To find [tex]\( f(a) \)[/tex], we substitute [tex]\( a = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(a) = f(2) = 3(2)^2 + 2 \][/tex]
[tex]\[ f(2) = 3 \cdot 4 + 2 \][/tex]
[tex]\[ f(2) = 12 + 2 \][/tex]
[tex]\[ f(2) = 14 \][/tex]
So, [tex]\( f(a) = 14 \)[/tex].
### Part (b) - Find [tex]\( f(a+h) \)[/tex]
To find [tex]\( f(a+h) \)[/tex], we substitute [tex]\( a = 2 \)[/tex] and [tex]\( h = 1 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(a + h) = f(2 + 1) = f(3) \][/tex]
[tex]\[ f(3) = 3(3)^2 + 2 \][/tex]
[tex]\[ f(3) = 3 \cdot 9 + 2 \][/tex]
[tex]\[ f(3) = 27 + 2 \][/tex]
[tex]\[ f(3) = 29 \][/tex]
So, [tex]\( f(a+h) = 29 \)[/tex].
### Part (c) - Find [tex]\( \frac{f(a+h) - f(a)}{h} \)[/tex]
To find the difference quotient, we use the values for [tex]\( f(a) \)[/tex] and [tex]\( f(a+h) \)[/tex]:
[tex]\[ \frac{f(a+h) - f(a)}{h} = \frac{f(3) - f(2)}{1} \][/tex]
[tex]\[ \frac{f(3) - f(2)}{1} = \frac{29 - 14}{1} \][/tex]
[tex]\[ \frac{29 - 14}{1} = \frac{15}{1} \][/tex]
[tex]\[ \frac{15}{1} = 15 \][/tex]
So, [tex]\( \frac{f(a+h) - f(a)}{h} = 15 \)[/tex].
### Summary
The answers to the questions are:
a.) [tex]\( f(a) = 14 \)[/tex]
b.) [tex]\( f(a+h) = 29 \)[/tex]
c.) [tex]\( \frac{f(a+h) - f(a)}{h} = 15 \)[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.